Visual as Language: An Explanation of the “Chocolajit” Wajit Packaging Design within the Context of Branding and Culture - Galuh Regita Pitaloka; Sri Retnoningsih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2026)
Packaging design plays a strategic role in enhancing the competitiveness of Small and Medium Enterprises (SMEs), particularly for regional souvenir products in West Java. This study examines the interactive packaging redesign of the Wajit Cililin product “Chocolajit” by the SOKARYA Team, which functions as an educational medium to foster cultural awareness and responsible behavior in post-consumption packaging management. Through the integration of Sundanese culture, visual elements, and Augmented Reality (AR) technology, the packaging is designed not only to be aesthetically appealing but also to provide educational value and promote sustainability. The use of eco-friendly materials, modular design, and interactive features strengthens local identity while reducing waste. Collaboration between designers and business actors is a key factor in realizing innovative and competitive packaging that supports the growth of culture-based and sustainable creative industries.